Post-treatment of a submerged anaerobic membrane bioreactor (SAMBR) saline effluent using powdered activated carbon (PAC) - Stuckey, David C.; Conteras, P. A.; Vyrides, Ioannis (My University, 2010)
Powdered activated carbon (PAC) was added to an effluent from a submerged anaerobic membrane bioreactor (SAMBR) treating saline wastewater as a post-treatment method. The adsorption of contaminants was carried out and key Freundlich isotherm parameters were evaluated. The results showed a reduction in dissolved organic carbon (DOC) in the effluent of over 80% after treatment with 1.7 g PAC/L. The composition of the effluent was determined by the use of size exclusion chromatography (SEC) and by GC–MS analysis. Most of the components of the effluent had a MW less than 1 kDa, and these were the hardest to eliminate by PAC adsorption. m-Aminophenylacetylene, cyclohexane 1,2,4 trimethyl and cholestan 3-one were found in the effluent, but could be removed by PAC adsorption. Finally, different methods for using PAC, with or without biomass, revealed that aerobic biomass enhanced the adsorption process resulting in higher DOC removals.
Keywords: Carbon, Activated; Adsorption; Bioreactors